ARE YOUR IDEAS REPRESENTED IN YOUR TEXTS? TRANSITIVITY ANALYSIS OF RECOUNT TEXTS - Yustika Nur Fajriah (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
Following the curriculum 2013’s demand that students are required to be able to deliver ideas by considering the context, this study is an attempt to analyze the student’s recount texts based on Halliday’s theory of transitivity. To achieve this aim, this study employed a qualitative research approach with a case study design. Specifically, six selected students’ recount texts were chosen to be analyzed. The analysis focuses on types of processes, participants, and circumstances. The result reveals that some of the students focused on describing places (relational process) instead of retelling the activities, meanwhile others have used the material process as the most dominant type of process yet did not evaluate the events (mental process). Therefore, text models, explicit teaching, as well as effective corrective feedback, are the alternatives to be taken into account in improving their capacities in writing this simplest text; recount text.